(NsTIHOTWORENIQ I PO\MY(B: [1912-1931] /s (N~ASTX (B1s - (NpASTERNAK(B, (NbORIS lEONIDOWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1989)
(Nw TOM WHODQT PO\TI^ESKIE PROIZWEDENIQ b(B.(Nl(B.(NpASTERNAKA (B1912-1931 (NGG(B. ((NsTIHOTWORENIQ IZ KNIG (B"(NpOWERH BARXEROW(B","(NsESTRA MOQ (B- (NVIZNX(B", "(NtEMY I WARIACII(B", "(NwTOROE ROVDENIE(B", (NPO\MY (B"(NwYSOKAQ BOLEZNX(B", "(NdEWQTXSOT PQTYJ GOD(B", "(NlEJTENANT {MIDT(B" (NI DR(B.)s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs